Investigating the influence of functional electrical stimulation on motor imagery related μ-rhythm suppression - Yakovlev, Lev; Syrov, Nikolay; Kaplan, Alexander (Frontiers in Neuroscience, 2023)
Motor Imagery (MI) is a well-known cognitive technique that utilizes the same neural circuits as voluntary movements. Therefore, MI practice is widely used in sport training and neurorehabilitation after strokes. The suppression of the μ-rhythm in electroencephalogram (EEG) is a conventional marker of sensorimotor cortical activation during motor imagery. However, the role of somatosensory afferentation in mental imagery processes is not yet clear. In this study, we investigated the impact of functional electrical stimulation (FES) on μ-rhythm suppression during and after motor imagery. Thirteen healthy experienced participants were asked to imagine their right hand grasping, while a 30channel EEG was recorded. FES was used to influence sensorimotor activation during motor imagery of the same hand. We evaluated cortical activation by estimating the μ-rhythm suppression index, which was assessed in three experimental conditions: MI, MI+FES, and FES. Our findings suggest that motor imagery enhanced by FES leads to a more prominent μ-rhythm suppression. These results suggest a direct effect of peripheral electrical stimulation on cortical activation, especially when combined with motor imagery.